Hypoglycaemia in type 2 diabetes exacerbates amyloid‐related proteins associated with dementia. Issue 2 (25th October 2020) - Moin, Abu Saleh Md; Al‐Qaissi, Ahmed; Sathyapalan, Thozhukat; Atkin, Stephen L.; Butler, Alexandra E.
Abstract: Aims: Hypoglycaemia in diabetes (T2D) may increase the risk of Alzheimer's disease (AD). We hypothesized that hypoglycaemia‐induced amyloid‐related protein changes would be exacerbated in T2D. Materials and methods: A prospective, parallel study in T2D (n = 23) and controls (n = 23). Subjects underwent insulin‐induced hypoglycaemia with blood sampling at baseline, hypoglycaemia and post‐hypoglycaemia; proteomic analysis of amyloid‐related proteins was undertaken. Results: At baseline, amyloid‐precursor protein (APP) ( P < .01) was elevated and alpha‐synuclein (SNCA) ( P < .01) reduced in T2D. At hypoglycaemia, amyloid P‐component ( P < .01) was elevated and SNCA ( P < .05) reduced in T2D; APP ( P < .01) and noggin ( P < .05) were elevated and SNCA ( P < .01) reduced in controls. In the post‐hypoglycaemia follow‐up period, APP and microtubule‐associated protein tau normalized in controls but showed a below‐baseline decrease in T2D; noggin normalized in both; SNCA normalized in T2D, with a below‐baseline decrease in controls. Conclusion: The AD‐associated protein pattern found in T2D, with basal elevated APP and reduced SNCA, was exaggerated by hypoglycaemia with increased APP and decreased SNCA. Additional AD‐associated protein levels that changed in response to hypoglycaemia, particularly in T2D, included amyloid P‐component, microtubule‐associated protein tau, apolipoproteins A1 and E3, pappalysin and noggin. These results are in accordance with the reported detrimental effects of hypoglycaemia.